Characterization of the novel HLA‐A*30:02:28 allele by sequencing‐based typing. (20th December 2021) - Elsermans, Vincent; Visentin, Jonathan; Top, Isabelle; Varlet, Pauline; Labalette, Myriam
Abstract : HLA‐A*30:02:28 differs from HLA‐A*30:02:01:01 by one nucleotide substitution in codon 47 in exon 2.